2020
DOI: 10.1371/journal.pone.0228465
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dietary behaviour in wheelchair users with spinal cord injury or lower limb amputation: Perspectives of rehabilitation professionals and wheelchair users

Abstract: ¶ Membership of the WHEELS-study group is provided in the Acknowledgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…This is significant because Holla et al. (2020) reported that boredom had a negative influence on dietary behaviour in wheelchair users with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is significant because Holla et al. (2020) reported that boredom had a negative influence on dietary behaviour in wheelchair users with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, caregivers focused on keeping individuals with higher cervical injuries active and busy so that they did not sleep all day or eat out of boredom. This is significant becauseHolla et al (2020) reported that boredom had a negative influence on dietary behaviour in wheelchair users with SCI.…”
mentioning
confidence: 99%
“…Participants also highlighted that as a result of the injury and subsequent bodily changes, these individuals have fewer opportunities to participate in leisure physical activities or exercise and more challenges in shopping and preparing meals. Similarly, among wheelchair users, function impairments and unadjusted kitchens were found to influence dietary behaviors [ 19 ], suggesting that the inability to prepare a healthy meal, due to either physical ability or not having an accessible kitchen, may lead this population to resort to unhealthier options. Future weight management studies may want to focus on identifying strategies to address the negative impacts that physical ability and mobility limitations have on both exercise and healthy eating.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that individuals feel restricted in healthy eating goals because they experience challenges independently cooking for themselves. Holla et al (2020) identified multiple barriers that complicate healthy eating behaviors, including inaccessible kitchens and challenges shopping for and cooking healthy meals, for example, demands on both time and energy consumption. Another reason for not focusing on healthy eating goals may be that food is a remaining source of enjoyment after injury and individuals with SCI do not want to give up this pleasure of food (Ehrlich-Jones et al, 2020).…”
Section: Discussionmentioning
confidence: 99%